Method for carry estimation of reduced-width multipliers - Liao Yen-Chin; Chang Hsie-Chia (My University, 2011)
A low-error reduced-width multiplier is provided by the present invention. The multiplier can dynamically compensate the truncation error. The compensation value is derived by the dependencies among the multiplier partial products, and thus, can be analyzed according to the multiplication type and the multiplier input statistics.